Preferences and educational expectations of young adults preparing for the final exams in English - Palankiewicz-Mitrut, Emilia (Free your mind: Reflections on language, literature and culture, 2022)
Language education among adults is becoming increasingly important. The result of this phenomenon is the fact that a large number of language courses are aimed at this age group. Adults start learning a foreign language because they want to improve their professional qualifications and find a better paid job in the future, or - as regards younger adults, pass their high school final exams and get the desired studies. The first part of this study presents the differences between teaching a foreign language to adults and children. Then, on the basis of the theory of motivators relating to undertaking educational activity by adults, the role of motivation in the educational process is shown. The next part of the work presents the results of a survey conducted among high school graduates from Poland and Romania concerning the preferences and needs of young adults in the context of language education. At the end, the conclusions regarding the previously described study are presented, with regard to the educational expectations of students both towards the subject itself, the teachers, and the teaching methods used by them. Young adults are a demanding group of students, because on the one hand, they pursue the learning goals set for them by the school or university, and on the other hand, they already have their own expectations regarding participation in the educational process. They feel an internal need to develop their own interests and acquire new skills, which may help them find their dream job in the future. Therefore, it is important that the teacher, treating his pupils individually, guides them appropriately, showing that learning can be both a necessity combined with an intellectual effort and a valuable experience.